Pre-curettage cerclage in a viable triplet cervical pregnancy: A case report and review of literature - Mahdavi, Atossa (Int J Reprod Biomed, 2019)
BACKGROUND: Cervical ectopic pregnancy (CEP) is a rare and dangerous form of ectopic pregnancy in which the blastocyst is installed within the endo-cervical canal. CEP diagnosis requires special awareness to evaluate patient precisely. Individualizing controversial medical and surgical management strategies is of importance in medical practice. CASE: A 35-year-old nulliparous woman on her 9th week of pregnancy was referred to our hospital with vaginal bleeding preliminary misdiagnosed as aborting intrauterine pregnancy. Transvaginal ultrasound revealed an empty uterus and a viable triplet pregnancy just below the level of internal os. Cervical curettage after cerclage suture placement procedure removed conception tissues completely. Consequently, in the next few hours vaginal bleeding decreased to minimal amount and vital signs remained within normal limits and there was no hematocrit change. On follow-up day 32, serum B-HCG became negative. CONCLUSION: CEP diagnosis requires special attention and awareness to evaluate patient precisely along with skillful assessment of possible risk factors. Lifesaving treatment beside fertility preservation was successful with pre-curettage cerclage.